Development of high sensitive radioimmunoassay and biosensor for human nocistatin - Suresh Kumar Shailaja. (2008)
In order to investigate possible relationships between NST and pain perception, highly sensitive and rapid detection methods and devices for human NST (hNST) are required. Analytical assays in research are progressing by the development of new, simple, rapid techniques, however bearing in mind that sometimes no viable match to conventional assays can be found due to their increased sensitivity and precision.